The Functions of Films for Children as Learning Media in Children's Education - Dyani Prades Pratiwi; Roma Kyo Kae Saniro; Andina Meutia Hawa (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
Children's interest in learning should be continuously enhanced. Selecting suitable learning media is very important to support the increased interest in learning. A film can be one of the learning media that offers advantages for achieving a quality children's education process. This study aims to discuss the functions of films for children in children's education. The method used is descriptive qualitative with literary studies techniques. The study results show that there are three functions of films for children as learning media, namely film as a media for language learning, film as a media for character building, and film as a media for introducing multiculturalism. Film can stimulate children's imagination so that children can think actively and creatively. However, the functions of films are inseparable from the role of parents and teachers in selecting films and methods or techniques for presenting films so that children remain active learners.